Keabsahan Jual Beli Hak Atas Tanah Kepada Warga Negara Asing di Desa Karangsuraga dan Desa Bulakanan, Cinangka, Banten - Mochammad Ridwan; Putri Ayu Maharani; Wibisono Oedoyo (CV. Doki Course and Training, 2024)
In community service activities in Karang Suraga Village and Bulakan Village, Cinangka Serang District, Banten, it can be observed that the Anyer area is an ecotourism area that is visited by many people, including foreign nationals. On the other hand, the knowledge of the community and village officials regarding the transfer of property rights to foreign citizens. This study will focus on discussing the transfer of property rights in the form of Nominees by Foreign Citizens. The method of community service activities is carried out by direct legal counseling to the community and village officials. This study was compiled based on the data obtained from these outreach activities and by using non-doctrinal legal study methods. This program was implemented on 29-30 March 2022. The results of this program concluded that the knowledge of village officials and the community was still very limited regarding legal issues. Although to overcome this problem, village officials have tried to find various solutions to legal problems in the community.